2022
DOI: 10.1111/jrh.12674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating policies to improve access to mental health services in rural areas

Abstract: Purpose:The United States Department of Veterans Affairs (VA) has gradually implemented policies to increase access to mental health care outside of VA medical centers. Most notably, this included requirements to offer mental health services at VAadministered community-based clinics in 2008 and increased access to VA-paid care in the community beginning in 2014. Our objective was to understand how mental health service use patterns changed for rural VA patients during this time. Methods:We developed a longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…In this study, rural and urban Hispanic VA patients had similar rates of mental health services use overall across the period of observation. In related work, we recently showed that following policy changes to increase mental health access in 2008 and 2014, rural Hispanic VA patients were more likely to use mental health services and received an equivalent number of visits to rural non‐Hispanics 24 . In this current work, we found similar rates of mental health access and a prominent trend of increased rates of mental health diagnosis in both rural and urban Hispanic patients comparing 2005‐2019.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, rural and urban Hispanic VA patients had similar rates of mental health services use overall across the period of observation. In related work, we recently showed that following policy changes to increase mental health access in 2008 and 2014, rural Hispanic VA patients were more likely to use mental health services and received an equivalent number of visits to rural non‐Hispanics 24 . In this current work, we found similar rates of mental health access and a prominent trend of increased rates of mental health diagnosis in both rural and urban Hispanic patients comparing 2005‐2019.…”
Section: Discussionsupporting
confidence: 68%
“…and received an equivalent number of visits to rural non-Hispanics. 24 In this current work, we found similar rates of mental health access and a prominent trend of increased rates of mental health diagnosis in both rural and urban Hispanic patients comparing 2005-2019. However, the rates of most mental health diagnoses were higher in urban Hispanic patients compared to rural Hispanic patients.…”
Section: F I G U R Esupporting
confidence: 66%
“…Defence families are those with a currently serving member, whereas Veteran families are those with an ex‐serving member (hereafter Defence families). Living in regional and rural Australian communities profoundly impacts the ability of residents to take advantage of delivery modalities and payment methods to access mental health services 4 despite having a high need for these services. Australian research reports that the Defence family members, especially partners of those deployed, experience unique caregiving stressors, poor marital adjustment and life satisfaction and significantly higher levels of depression, stress and anxiety, when compared with population norms 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, some have posed solutions like virtual care options such as video telehealth to improve access to specialty care 10 ; however, this solution only partially meets this need. 11 Many rural residents prefer in-person modalities and/or lack sufficient access to broadband for high-quality video conference, and many healthcare needs require in-person assessment and treatment, making recruitment and retention of providers in these areas important elements to addressing rural health disparities. 12 Many programs and funding mechanisms have been introduced to support rural health workforce development over the past 3 decades.…”
Section: Introductionmentioning
confidence: 99%